Data Storage Security and Privacy in Mobile Cloud Computing Using Hierarchical Attribute Based Encryption (HABE) - Paka, Tejaswini; Divya, Sree (International Journal of Computer Sciences and Engineering, 2019)
In spite of the fact that the electronic advances have experienced quick improvements as of late, cell phones, for example, PDAs are still similarly powerless rather than work areas as far as computational ability, stockpiling and so on, and are not ready to meet the expanding requests from versatile clients. By incorporating portable figuring and distributed computing, versatile distributed computing (MCC) extraordinarily expands the limit of the portable applications, however it additionally acquires numerous difficulties in distributed computing, e.g., information security and information honesty. In this paper, we use a few cryptographic natives, for example, another composes based intermediary re-encryption to plan a protected and proficient information circulation framework in MCC, which gives information security, information respectability, information verification, and adaptable information appropriation with get to control. Contrasted with customary cloud-based information stockpiling frameworks, our framework is a lightweight and effortlessly deployable answer for portable clients in MCC since no confided in outsiders are included and every versatile client just needs to keep short mystery keys comprising of three gathering components for every single cryptographic activity. At last, we present broad execution examination and exact investigations to exhibit the security, versatility, and productivity of our proposed framework.